Molybdenum-bismuth-iron catalysts, methods for their preparation and use, and processes for the ammoxidation of propylene
Patent Information
- Application Number
- CN202311508482.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-11-13
AI Technical Summary
[0014]具有本发明组成的催化剂具有特定的晶相(激光拉曼峰的特征),不仅在较高的烯烃(尤其丙烯)负荷下具有较高的腈类化合物(尤其丙烯腈)收率,而且催化剂稳定性优异,提高装置的生产效率和经济效益。
Smart Images

Figure CN119972104B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalysts, specifically to a molybdenum-bismuth-iron catalyst, its preparation method and application, and a method for the ammoxidation of propylene. Background Technology
[0002] Acrylonitrile is an important organic chemical raw material, produced through the ammoxidation of propylene. To obtain highly active and selective fluidized bed catalysts, researchers have continuously explored and made a series of improvements. These improvements mostly involve the active composition of the catalyst, focusing on the combination of active components to enhance the catalyst's activity and selectivity, thereby increasing the single-pass yield of acrylonitrile and improving production load.
[0003] After more than 50 years of development, acrylonitrile production via ammonia oxidation has seen a continued demand gap in recent years. The main trend in acrylonitrile production is to build new large-scale plants to achieve economies of scale, further reducing raw material and energy consumption while increasing production capacity. Domestic acrylonitrile plant construction has seen a significant increase in capacity, and once completed, plant production capacity will nearly balance market demand. Therefore, future competition among acrylonitrile plants will not only focus on the economic benefits of acrylonitrile production efficiency but also on prioritizing environmentally friendly and clean production, ensuring the long-term stable operation of acrylonitrile catalysts, reducing maintenance cycles, and thus improving the overall economic efficiency of the plant.
[0004] When expanding existing acrylonitrile plants, the catalyst loading must be limited. Therefore, the replacement catalyst must maintain a high acrylonitrile yield under higher propylene loads. Once the reactor size and production capacity are determined, the amount of catalyst loaded is related to the catalyst's load capacity, i.e., WWH (While the catalyst can withstand). WWH is defined as the number of tons of propylene processed per ton of catalyst per hour. When the reactor feed rate increases, if the catalyst load remains constant, the catalyst loading must also increase accordingly. However, the cooling water pipe height in the original fluidized bed reactor design is insufficient, so the fluidization height of the catalyst in the reactor may exceed the height of the cooling water pipes. Furthermore, the increased reactor feed rate leads to a significant increase in the operating linear velocity. The combined effect of these two changes may cause an increase in the dilute phase temperature of the reactor, resulting in increased carbon dioxide production and decreased acrylonitrile selectivity. Therefore, a catalyst with a higher WWH can prevent these problems.
[0005] However, the existing technology does not involve a catalyst capable of producing acrylonitrile under high propylene loading and high reaction pressure. Summary of the Invention
[0006] The purpose of this invention is to overcome the problem that existing ammonia oxidation catalysts cannot produce acrylonitrile under high propylene loading and high reaction pressure. This invention provides a molybdenum-bismuth-iron catalyst, its preparation method and application, and a method for ammonia oxidation of propylene. This catalyst can produce nitrile compounds under high olefin loading and high reaction pressure, with high yield and good stability.
[0007] To achieve the above objectives, a first aspect of the present invention provides a molybdenum-bismuth-iron catalyst, the catalyst comprising a support and an active component, said active component having a composition as shown in Formula A. a B b C c Fe d Ni e Bi f Mo 12.5 O x The composition is shown in the formula, where A is at least one alkali metal element, B is at least one alkaline earth metal element, transition metal element, and Group IIIA metal element, and C is at least one lanthanide metal element; the value of a ranges from 0.01 to 2.50; the value of b ranges from 0.10 to 10.00; the value of c ranges from 0.01 to 5.00; the value of d ranges from 0.01 to 5.00; the value of e ranges from 1.00 to 10.00; the value of f ranges from 0.01 to 5.00; and x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst. In the laser Raman spectrum of the catalyst, at 785±2 cm⁻¹... -1 956±2cm -1 The strength ratio at that location is 0.55-0.80.
[0008] A second aspect of the present invention provides a method for preparing the molybdenum-bismuth-iron catalyst described above, the method comprising:
[0009] (1) Prepare a precursor containing element A and a support, wherein the precursor contains free [H] + The concentration is 10 -10.5 -10 -8.4 mol / L; the particle size of the carrier in the precursor is 5-15 nm, and the specific surface area is 150-650 m² / L. 2 / g;
[0010] (2) The precursor is mixed with a solution containing Mo, C, B, Fe, Bi and Ni to obtain a slurry, which is then heat-treated, dried and calcined.
[0011] A third aspect of the present invention provides the application of the catalyst described in the first aspect of the present invention in the ammoxidation reaction of olefins.
[0012] A fourth aspect of the present invention provides a method for the ammoxidation of propylene, the method comprising: reacting propylene feedstock, ammonia feedstock and oxygen feedstock in contact under catalytic conditions; wherein the catalyst is the catalyst described in the first aspect of the invention.
[0013] Through the above technical solution, the present invention has the following advantages:
[0014] The catalyst with the composition of this invention has a specific crystal phase (characteristic of laser Raman peaks), which not only has a high yield of nitrile compounds (especially acrylonitrile) under high olefin (especially propylene) loading, but also has excellent catalyst stability, thereby improving the production efficiency and economic benefits of the plant. Attached Figure Description
[0015] Figure 1 These are laser Raman comparison images of the catalysts prepared in Example 1, Comparative Example 1, and Comparative Example 2.
[0016] Figure 2 This is a laser Raman image of the catalyst prepared in Example 2. Detailed Implementation
[0017] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0018] This invention provides a molybdenum-bismuth-iron catalyst, which comprises a support and an active component, wherein the active component has the properties of formula A. a B b C c Fe d Ni e Bi f Mo 12.5 O x The composition is shown in the formula, where A is at least one alkali metal element, B is at least one alkaline earth metal element, transition metal element, and Group IIIA metal element, and C is at least one lanthanide metal element; the value of a ranges from 0.01 to 2.50; the value of b ranges from 0.10 to 10.00; the value of c ranges from 0.01 to 5.00; the value of d ranges from 0.01 to 5.00; the value of e ranges from 1.00 to 10.00; the value of f ranges from 0.01 to 5.00; and x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst. In the laser Raman spectrum of the catalyst, at 785±2 cm⁻¹... -1 956±2cm-1 The strength ratio at the point is 0.55-0.80, for example, it can be 0.55, 0.57, 0.60, 0.65, 0.70, 0.75, 0.78, or 0.80, preferably 0.57-0.78.
[0019] The catalyst characterized by this invention not only exhibits high yields of nitrile compounds (especially acrylonitrile) under high olefin (especially propylene) loadings, but also possesses a specific crystal phase, demonstrating excellent stability and improving the production efficiency and economic benefits of the plant.
[0020] According to a preferred embodiment of the present invention, formula A a B b C c Fe d Ni e Bi f Mo 12.5 O x In this context, A is selected from at least one of Li, Na, K, Rb, and Cs, preferably at least one of K, Rb, and Cs.
[0021] According to a preferred embodiment of the present invention, formula A a B b C c Fe d Ni e Bi f Mo 12.5 O x In this mixture, B is selected from at least one of W, Ga, Nb, Mg, Ca, Cr and Co, preferably at least one of W, Mg, Ca, Cr and Co.
[0022] According to a preferred embodiment of the present invention, formula A a B b C c Fe d Ni e Bi f Mo 12.5 O x In this context, C is selected from at least one of La, Ce, Nd, and Pr, preferably at least one of La, Ce, and Nd.
[0023] According to a preferred embodiment of the present invention, formula A a B b C c Fe d Ni e Bi f Mo 12.5 O xIn the given equation, the value of a ranges from 0.05 to 1.50; the value of b ranges from 1.50 to 9.00; the value of c ranges from 0.05 to 3.50; the value of d ranges from 0.05 to 3.00; the value of e ranges from 1.50 to 9.00; and the value of f ranges from 0.05 to 3.00.
[0024] In this invention, there are no special requirements for the content of each component of the catalyst. According to a preferred embodiment of the present invention, the catalyst comprises, by weight of total catalyst, 30-70% support and 30-70% active component. The present invention uses a 50% support and 50% active component as an example to illustrate the advantages of the present invention.
[0025] In this invention, the carrier can be a conventional choice in the art. According to a preferred embodiment of the invention, the carrier is selected from at least one of silicon dioxide, alumina, titanium dioxide, and zirconium oxide. This invention uses silicon dioxide as an example to illustrate its advantages.
[0026] This invention provides a method for preparing a molybdenum-bismuth-iron catalyst, the method comprising:
[0027] (1) Prepare a precursor containing element A and a support, wherein the precursor contains free [H] + The concentration is 10 -10.5 -10 -8.4 mol / L; the particle size of the carrier in the precursor is 5-15 nm, and the specific surface area is 150-650 m² / L. 2 / g;
[0028] (2) The precursor is mixed with a solution containing Mo, C, B, Fe, Bi and Ni to obtain a slurry, which is then heat-treated, dried and calcined.
[0029] The molybdenum-bismuth-iron catalyst prepared by the method of this invention not only has a high yield of nitrile compounds (especially acrylonitrile) under high olefin (especially propylene) loading, but also has a specific crystal phase and excellent stability, thereby improving the production efficiency and economic benefits of the equipment.
[0030] According to a preferred embodiment of the present invention, step (1) of preparing the precursor includes: dissolving source A to obtain solution I, and mixing solution I, pH adjuster and carrier source to obtain the precursor.
[0031] According to a preferred embodiment of the present invention, the pH adjuster is selected from at least one of ammonia water, ammonia gas, and alkali metal hydroxides.
[0032] According to a preferred embodiment of the present invention, step (2) includes: dissolving the Mo source to obtain solution II; dissolving the C source to obtain solution III; dissolving the B source, Fe source, Bi source, and Ni source to obtain solution IV; and then adding materials II, III, and IV to the precursor to obtain a slurry, followed by heat treatment, drying, and calcination.
[0033] By adopting the aforementioned preferred preparation method, the activity and stability of the catalyst can be further improved.
[0034] In this invention, the heat treatment conditions can be conventionally chosen in the art. According to a preferred embodiment of the invention, the heat treatment conditions include: a temperature of 80-150°C and a time selected according to temperature variations, ranging from 10-60 minutes. This invention uses a heat treatment at 110°C for 30 minutes as an example to illustrate its advantages.
[0035] In this invention, each element source refers to the soluble compound of the corresponding element.
[0036] According to a preferred embodiment of the present invention, the precursor contains free [H] + The concentration is 10 -10.2 -10 - 8.5 mol / L; the particle size of the carrier in the precursor is 6-13 nm; the specific surface area is 200-600 m² / L. 2 / g. By adopting the aforementioned preferred scheme, the activity and stability of the catalyst can be further improved.
[0037] According to a preferred embodiment of the present invention, the drying method is spray drying, and the preferred conditions for spray drying include: water evaporation rate of 7-13 L / h;
[0038] In this invention, the calcination conditions can be conventionally selected in the art. According to a preferred embodiment of the invention, the calcination conditions include: calcination at 550-680°C for 0.5-5 hours in an oxygen-containing atmosphere.
[0039] According to a preferred embodiment of the present invention, the roasting is carried out in a rotary roasting furnace, and the oxygen-containing atmosphere may be, for example, air.
[0040] This invention provides an application of the catalyst described herein in the ammoxidation reaction of olefins.
[0041] When the molybdenum-bismuth-iron catalyst of the present invention is applied to the ammoxidation reaction of olefins, it not only has a high yield of nitrile compounds (especially acrylonitrile) under a high olefin (especially propylene) load, but also has excellent stability, and the production efficiency and economic benefits of the equipment are good.
[0042] This invention provides a method for the ammoxidation of propylene, the method comprising: reacting propylene feedstock, ammonia feedstock and oxygen feedstock in contact under catalytic conditions; wherein the catalyst is the catalyst described in this invention.
[0043] According to a preferred embodiment of the present invention, the conditions for the contact reaction include: the molar ratio of propylene feedstock (based on propylene): ammonia feedstock (based on ammonia): oxygen feedstock (based on oxygen) is 1:1.05-1.35:1.6-2.6, preferably 1:1.1-1.3:1.8-2.4.
[0044] According to a preferred embodiment of the present invention, the conditions for the contact reaction include: a reaction temperature of 400-480°C, preferably 410-450°C.
[0045] According to a preferred embodiment of the present invention, the conditions for the contact reaction include: a reaction pressure of 0.02-0.15 MPaG, preferably 0.03-0.09 MPaG.
[0046] According to a preferred embodiment of the present invention, the conditions for the contact reaction include a weight hourly space velocity of 0.04-0.12 h⁻¹. -1 Preferably 0.05-0.10h -1 .
[0047] This invention utilizes a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The advantages of this invention will be illustrated by taking the raw material ratio (moles) C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0 as an example.
[0048] The present invention will be described in detail below through embodiments.
[0049] In the following embodiments:
[0050] Laser Raman spectroscopy was performed on a French Lab Ram confocal laser-micro Raman spectrometer. The excitation light was a He-Ne laser with a wavelength of 632.8 nm, a power of 3.0 mV, and a resolution of 1 cm⁻¹. -1 ;
[0051] The specific surface area of the precursor is determined by measuring the number of silanol groups using a titration method and then calculating the specific surface area using an empirical formula.
[0052] The precursor particle size was determined using a nanoparticle size analyzer.
[0053] Free [H + The concentration was measured using a pH meter.
[0054] All raw materials are commercially available.
[0055] Example 1
[0056] 1. Catalyst Preparation
[0057] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I, 25% ammonia solution, and 40% silica sol (by weight) were mixed to obtain a precursor. The particle size of the carrier in the precursor was measured to be 13 nm, and the specific surface area was 450 m². 2 / g, free [H + The concentration is 10 -10.0 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining in an air atmosphere in a rotary calciner (mm) at 585°C for 2.0 hours to obtain the following composition, by mass fraction:
[0058] 50% K 0.80 Mg 3.00 Nd 2.50 Fe 1.90 Ni 5.60 Bi 1.50 Mo 12.5 O x +50% SiO2
[0059] The measured laser Raman spectrum of the catalyst is attached. Figure 1 It can be seen that at 785cm -1 956cm -1 The peak intensity ratio at that location is 0.69.
[0060] 2. Catalyst Application
[0061] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0062] The results are shown in Table 1.
[0063] Example 2
[0064] 1. Catalyst Preparation
[0065] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I, 25% ammonia solution, and 40% silica sol (by weight) were mixed to obtain a precursor. The particle size of the carrier in the precursor was measured to be 5 nm, and the specific surface area was 650 m² / g. 2 / g, free [H + The concentration is 10 -10.0 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining in an air atmosphere in a rotary calciner (mm) at 585°C for 2.0 hours to obtain the following composition, by mass fraction:
[0066] 50% K 0.80 Mg 3.00 Nd 2.50 Fe 1.90 Ni 5.60 Bi 1.50 Mo 12.5 O x +50% SiO2
[0067] The laser Raman spectrum of the catalyst was measured and Figure 1 Similarly, at 785cm -1 956cm -1 The peak intensity ratio at that location is 0.68.
[0068] 2. Catalyst Application
[0069] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h.-1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0070] The results are shown in Table 1.
[0071] Example 3
[0072] 1. Catalyst Preparation
[0073] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I, 25% ammonia solution, and 40% silica sol (by weight) were mixed to obtain a precursor. The particle size of the carrier in the precursor was measured to be 15 nm, and the specific surface area was 450 m². 2 / g, free [H + The concentration is 10 -8.5 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining in an air atmosphere in a rotary calciner (mm) at 585°C for 2.0 hours to obtain the following composition, by mass fraction:
[0074] 50% K 0.80 Mg 3.00 Nd 2.50 Fe 1.90 Ni 5.60 Bi 1.50 Mo 12.5 O x +50% SiO2
[0075] The laser Raman spectrum of the catalyst was measured and Figure 1 Similarly, at 785cm -1 956cm -1 The peak intensity ratio at that location is 0.57.
[0076] 2. Catalyst Application
[0077] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0078] The results are shown in Table 1.
[0079] Example 4
[0080] 1. Catalyst Preparation
[0081] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I, 25% ammonia solution, and 40% silica sol (by weight) were mixed to obtain a precursor. The particle size of the carrier in the precursor was measured to be 13 nm, and the specific surface area was 450 m². 2 / g, free [H + The concentration is 10 -10.0 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, gallium nitrate Ga(NO3)3·9H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining in an air atmosphere in a rotary calciner (mm) at 585°C for 2.0 hours to obtain the following composition, by mass fraction:
[0082] 50% K 0.80 Ga 3.00 Nd 2.50 Fe 1.90 Ni 5.60 Bi 1.50 Mo 12.5 O x +50% SiO2
[0083] The measured laser Raman spectrum of the catalyst is shown in the appendix. Figure 1 Similarly, at 785cm -1 956cm -1 The peak intensity ratio at that location is 0.79.
[0084] 2. Catalyst Application
[0085] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0086] The results are shown in Table 1.
[0087] Example 5
[0088] 1. Catalyst Preparation
[0089] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I, 25% ammonia solution, and 40% silica sol (by weight) were mixed to obtain a precursor. The particle size of the carrier in the precursor was measured to be 13 nm, and the specific surface area was 450 m². 2 / g, free [H + The concentration is 10 -10.4 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining in an air atmosphere in a rotary calciner (mm) at 585°C for 2.0 hours to obtain the following composition, by mass fraction:
[0090] 50% K 0.80 Mg 3.00 Nd 2.50 Fe 1.90 Ni 5.60 Bi 1.50 Mo 12.5 O x +50% SiO2
[0091] The laser Raman spectrum of the catalyst and its associated spectra were measured. Figure 1 Similarly, at 785cm -1 956cm -1The peak intensity ratio at that location is 0.80.
[0092] 2. Catalyst Application
[0093] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0094] The results are shown in Table 1.
[0095] Example 6
[0096] 1. Catalyst Preparation
[0097] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I, 25% ammonia solution, and 40% silica sol (by weight) were mixed to obtain a precursor. The particle size of the carrier in the precursor was measured to be 15 nm, and the specific surface area was 450 m². 2 / g, free [H + The concentration is 10 -10.0 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining in an air atmosphere in a rotary calciner (mm) at 585°C for 2.0 hours to obtain the following composition, by mass fraction:
[0098] 50% K 0.80 Mg 3.00 Nd 2.50 Fe 1.90 Ni 5.60 Bi 1.50 Mo 12.5 O x +50% SiO2
[0099] The laser Raman spectrum of the catalyst and its associated spectra were measured. Figure 1Similarly, at 785cm -1 956cm -1 The peak intensity ratio at that location is 0.56.
[0100] 2. Catalyst Application
[0101] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0102] The results are shown in Table 1.
[0103] Example 7
[0104] 1. Catalyst Preparation
[0105] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I was mixed with a 40% (w / w) silica sol, and ammonia gas was introduced to obtain a precursor. The particle size of the carrier in the precursor was measured to be 15 nm, and the specific surface area was 450 m². 2 / g, free [H + The concentration is 10 -10.4 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining in an air atmosphere in a rotary calciner (mm) at 585°C for 2.0 hours to obtain the following composition, by mass fraction:
[0106] 50% K 0.80 Mg 3.00 Nd 2.50 Fe 1.90 Ni 5.60 Bi 1.50 Mo 12.5 O x +50% SiO2
[0107] The laser Raman spectrum of the catalyst and its associated spectra were measured. Figure 1 Similarly, at 785cm -1 956cm -1 The peak intensity ratio at that location is 0.69.
[0108] 2. Catalyst Application
[0109] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0110] The results are shown in Table 1.
[0111] Comparative Example 1
[0112] 1. Catalyst Preparation
[0113] Water was added to potassium hydroxide and heated to dissolve it, yielding material I; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O is dissolved in hot water at 80℃ to obtain material II; Bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O are mixed, dissolved in water by heating, and this is material III; Neodymium nitrate Nd(NO3)3·6H2O is added to water, dissolved by heating, and this is material IV.
[0114] Material I was mixed with silica sol with a weight concentration of 40%. The particle size of the carrier in the precursor was measured to be 25 nm, and the specific surface area was 100 m². 2 / g, free [H + The concentration is 10 -9.3 mol / L; Materials II and III were added sequentially under stirring, followed by material IV to obtain a catalyst slurry. The slurry was heat-treated at 110°C for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer using conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was calcined in a rotary calcining furnace (mm) at 585°C for 2.0 hours to obtain a catalyst composition, by mass fraction:
[0115] 50% K 0.80 Mg 3.00 Nd 2.50 Fe 1.90 Ni 5.60 Bi 1.50 Mo12.5 O x +50% SiO2
[0116] The laser Raman spectrum of the catalyst was measured at 785 cm⁻¹. -1 956cm -1 The peak intensity ratio at that location is 0.42.
[0117] 2. Catalyst Application
[0118] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0119] The results are shown in Table 1.
[0120] Comparative Example 2
[0121] 1. Catalyst Preparation
[0122] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I, 25% ammonia solution, and 40% silica sol (by weight) were mixed to obtain a precursor. The particle size of the carrier in the precursor was measured to be 3 nm, and the specific surface area was 700 m². 2 / g, free [H + The concentration is 10 -9.0 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining in an air atmosphere in a rotary calciner (mm) at 585°C for 2.0 hours to obtain the following composition, by mass fraction:
[0123] 50% K 0.80 Mg 3.00 Nd 2.50 Fe 1.90 Ni 5.60Bi 1.50 Mo 12.5 O x +50% SiO2
[0124] The laser Raman spectrum of the catalyst was measured at 785 cm⁻¹. -1 956cm -1 The peak intensity ratio at that location is 0.52.
[0125] 2. Catalyst Application
[0126] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0127] The results are shown in Table 1.
[0128] Comparative Example 3
[0129] 1. Catalyst Preparation
[0130] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I, 25% ammonia solution, and 40% silica sol (by weight) were mixed to obtain a precursor. The particle size of the carrier in the precursor was measured to be 35 nm, and the specific surface area was 90 m². 2 / g, free [H + The concentration is 10 -10.2 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining in an air atmosphere in a rotary calciner (mm) at 585°C for 2.0 hours to obtain the following composition, by mass fraction:
[0131] 50% K 0.80 Mg 3.00 Nd 2.50 Fe1.90 Ni 5.60 Bi 1.50 Mo 12.5 O x +50% SiO2
[0132] The laser Raman spectrum of the catalyst was measured at 785 cm⁻¹. -1 956cm -1 The peak intensity ratio at that location is 0.16.
[0133] 2. Catalyst Application
[0134] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0135] The results are shown in Table 1.
[0136] Comparative Example 4
[0137] 1. Catalyst Preparation
[0138] Water was added to potassium hydroxide and heated to dissolve it, yielding solution I. Solution I, 25% ammonia solution, and 40% silica sol (by weight) were mixed to obtain a precursor. The particle size of the carrier in the precursor was measured to be 13 nm, and the specific surface area was 450 m². 2 / g, free [H + The concentration is 10 -10.0 mol / L; ammonium heptamolybdate (NH4)6Mo7O 24 • 4H2O was dissolved in hot water at 80℃ to obtain material II; neodymium nitrate Nd(NO3)3·6H2O was added to water and heated to dissolve to obtain material III; bismuth nitrate Bi(NO3)3·5H2O, magnesium nitrate Mg(NO3)2·6H2O, nickel nitrate Ni(NO3)2·6H2O, and iron nitrate Fe(NO3)3·9H2O were mixed, dissolved in water, and heated to obtain material IV; then materials II, III, and IV were added to the precursor to obtain a catalyst slurry. The slurry was heat-treated at 110℃ for 30 minutes, and then the heat-treated slurry was subjected to microsphere forming in a spray dryer under the condition of water evaporation rate of 10L / h according to conventional methods. Finally, microspheres with an inner diameter of 89 mm and a length of 1700 mm were formed. The catalyst was prepared by calcining the catalyst in a nitrogen atmosphere at 585°C for 2.0 hours in a rotary calcining furnace (mm) with a diameter of 100 mm.
[0139] 2. Catalyst Application
[0140] The reaction conditions are: A millimeter-sized fluidized bed reactor was used, with a reaction temperature of 430℃, a reaction pressure of 84 kPaG, a catalyst loading of 400 g, and a catalyst propylene loading (WWH) of 0.09 h. -1 The raw material ratio (moles) is C3H6 / NH3 / oxygen = 1 / 1.25 / 2.0.
[0141] The results are shown in Table 1.
[0142] Table 1
[0143]
[0144] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A molybdenum-bismuth-iron catalyst, characterized in that, The catalyst comprises a support and an active component, said active component having the properties of formula A. a B b C c Fe d Ni e Bi f Mo 12.5 O x The composition shown is as follows. In the formula, A is selected from at least one of Li, Na, K, Rb and Cs; B is selected from at least one of W, Ga, Nb, Mg, Ca, Cr and Co; and C is selected from at least one of La, Ce, Nd and Pr. The value of a ranges from 0.01 to 2.50; the value of b ranges from 0.10 to 10.00; the value of c ranges from 0.01 to 5.00; the value of d ranges from 0.01 to 5.00; the value of e ranges from 1.00 to 10.00; the value of f ranges from 0.01 to 5.00; and x is the total number of oxygen atoms required to satisfy the oxidation states of each element in the catalyst. In the laser Raman spectrum of the catalyst, at 785±2 cm⁻¹ -1 956±2cm -1 The strength ratio at that location is 0.57-0.78; The preparation method of the molybdenum-bismuth-iron catalyst includes: (1) Prepare a precursor containing element A and a support, wherein free [H] in the precursor + The concentration is 10 -10.5 -10 -8.4 mol / L; the particle size of the carrier in the precursor is 5-15 nm, and the specific surface area is 150-650 m². 2 / g; (2) The precursor is mixed with a solution containing Mo, C, B, Fe, Bi and Ni to obtain a slurry, which is then heat-treated, dried and calcined. The calcination conditions include: calcination at 550-680℃ for 0.5-5 hours in an oxygen-containing atmosphere.
2. The catalyst according to claim 1, wherein, Statement A a B b C c Fe d Ni e Bi f Mo 12.5 O x Inside, A is selected from at least one of K, Rb, and Cs; and / or B is selected from at least one of W, Mg, Ca, Cr, and Co; and / or C is selected from at least one of La, Ce, and Nd; and / or The value range of a is 0.05-1.50; the value range of b is 1.50-9.00; the value range of c is 0.05-3.50; the value range of d is 0.05-3.00; the value range of e is 1.50-9.00; and the value range of f is 0.05-3.
00.
3. The catalyst according to claim 1, wherein, The catalyst comprises, by total mass, 30-70% of a support and 30-70% of an active component.
4. The catalyst according to claim 1, wherein, The carrier is selected from at least one of silicon dioxide, aluminum oxide, titanium oxide, and zirconium oxide.
5. The catalyst according to claim 1, wherein, In step (1), the steps for preparing the precursor include: dissolving source A to obtain solution I, and mixing solution I, pH adjuster and carrier source to obtain the precursor; Step (2) includes: dissolving the Mo source to obtain solution II; dissolving the C source to obtain solution III; dissolving the B source, Fe source, Bi source, and Ni source to obtain solution IV; then adding material II, material III, and material IV to the precursor to obtain a slurry, followed by heat treatment, drying, and calcination.
6. The catalyst according to claim 1, wherein, Free [H] in the precursor + The concentration is 10 -10.2 -10 -8.5 mol / L; the particle size of the carrier in the precursor is 6-13 nm, and the specific surface area is 200-600 m² / L. 2 / g; and / or The drying conditions include an evaporation rate of 7-13 L / h for water.
7. The use of the catalyst according to any one of claims 1-6 in the ammoxidation reaction of olefins.
8. A method for the ammoxidation of propylene, characterized in that, The method includes: reacting propylene feedstock, ammonia feedstock and oxygen feedstock in contact under catalytic conditions; The catalyst is the catalyst according to any one of claims 1-6.
9. The method according to claim 8, wherein, The conditions for the contact reaction include: The molar ratio of propylene feedstock (based on propylene): ammonia feedstock (based on ammonia): oxygen feedstock (based on oxygen) is 1:1.05-1.35:1.6-2.6; and / or The reaction temperature is 400-480℃; and / or The reaction pressure is 0.02-0.15 MPaG; and / or The weight hourly space velocity is 0.04-0.12 h⁻¹. -1 .
10. The method according to claim 9, wherein, The conditions for the contact reaction include: The molar ratio of propylene feedstock (based on propylene): ammonia feedstock (based on ammonia): oxygen feedstock (based on oxygen) is 1:1.1-1.3:1.8-2.4; and / or The reaction temperature is 410-450℃; and / or The reaction pressure is 0.03-0.09 MPaG; and / or The weight hourly space velocity is 0.05-0.10 h⁻¹. -1 .
Citation Information
Patent Citations
Catalyst for preparing acrylonitrile through propylene ammoxidation as well as preparation method and application of catalyst
CN115501882A
Catalyst and method for producing compound using gas phase oxidation reaction using the catalyst
CN116963833A
